Severe Unexplained Relative Hypotension and Bradycardia in the Emergency Department. (5th March 2014) - Kharod, Shivam; Norman, Candice; Ryan, Matthew; Hoelle, Robyn M.
Abstract : A precipitous episode of hypotension with concomitant bradycardia is a true medical emergency especially in patients with chronic hypertension and often requires hospitalization for detailed interrogation of the underlying causes. We describe herein a case of a patient with chronic labile hypertension who presented to the ED with a sharp drop in blood pressure and heart rate which was not simply explained by an antihypertensive overdose but more so by an aggregate of the patient's multiple chronic medical conditions. This report highlights the complexities of treating simultaneous hypotension and bradycardia and the importance of discerning the underpinnings of the causes including past medical issues, patient medications, and the timeline of key events leading to the issue at hand.